Learning Space Quality Monitoring: Sensing the Unseen Factor - Nor Azhar, Ahmad; Rahmah, Mokhtar; Roslina, Abd Hamid; Fauziah, Zainuddin; Amirul Husni, Abd. Ghaffar; Nazira, Azman (Centre for Teaching and Learning, IIUM and Darul Syakir Enterprise, 2018)
Providing the best infrastructure for learning in university is the most important job. Administrator tends to look after the physical infrastructure rather than unseen matters. Recently, no device or scheme available to detect and prevent with monitoring the learning space quality. 150 students from multiple courses had participated in the learning investigations. The sites for investigations are the lecture hall, computer laboratory, and library. In the same investigations, we activate the HeDoo devices which detecting air particles which theoretically affect the quality of learning. Even though the site looks cozy and breathable, it showed students have a problem, especially in knowledge understanding, memorizing, and focusing. The three unseen major factors influencing the learning quality are humidity (95%), temperature (93%), and carbon dioxide (92%). This finding is beneficial to educational infrastructure planning and may provide a good outcome on students’ performance. Further analysis will be run especially on minor factors.